2009
DOI: 10.1091/mbc.e08-07-0776
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-Coil–Mediated Dimerization Is Not Required for Myosin VI to Stabilize Actin during Spermatid Individualization inDrosophila melanogaster

Abstract: Myosin VI is a pointed-end-directed actin motor that is thought to function as both a transporter of cargoes and an anchor, capable of binding cellular components to actin for long periods. Dimerization via a predicted coiled coil was hypothesized to regulate activity and motor properties. However, the importance of the coiled-coil sequence has not been tested in vivo. We used myosin VI's well-defined role in actin stabilization during Drosophila spermatid individualization to test the importance in vivo of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Strictly speaking, however, binding of myosin VI to Dab2 pep is not equivalent to activation. Activation requires the release of autoinhibition of full-length myosin VI, allowing it to interact with actin in either a transport (56) or anchoring role (16). To demonstrate activation of myosin VI in vivo, we showed that myosin VI recruited to peroxisomes via our engineered positive control construct LOVDab +ctrl stalls these organelles.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Strictly speaking, however, binding of myosin VI to Dab2 pep is not equivalent to activation. Activation requires the release of autoinhibition of full-length myosin VI, allowing it to interact with actin in either a transport (56) or anchoring role (16). To demonstrate activation of myosin VI in vivo, we showed that myosin VI recruited to peroxisomes via our engineered positive control construct LOVDab +ctrl stalls these organelles.…”
Section: Discussionmentioning
confidence: 96%
“…Dissociation of the CBD from the head both frees the head to bind tightly to actin and exposes dimerization sites throughout the tail domain of myosin VI, allowing it to become a processive dimer (13)(14)(15). In some cases, myosin VI could conceivably function as a monomer, for example when fulfilling its role as a membrane tether during spermatid individualization (16). If this is the case, more work is needed to elucidate the cellular signals that determine its oligomeric state at each site of action.…”
mentioning
confidence: 99%
“…However, under certain conditions, for example, when it acts to regulate actin stabilisation during spermatid individualisation, myosin VI can fully function when it lacks the ability to dimerise. Under these circumstances it remains bound to actin for long periods, thus functioning as an actin tether (Noguchi et al, 2009;Noguchi et al, 2006). Furthermore, it has been suggested that, as load is increased on myosin VI, it switches from its transport function to an anchoring function (Altman et al, 2004), such as at the base of microvilli, stereocilia and on vesicles in the terminal synaptic bouton (Hertzano et al, 2008;Kisiel et al, 2011;Sakurai et al, 2011;Seiler et al, 2004).…”
Section: Myosin VImentioning
confidence: 99%
“…Myosin-6 mutants have reduced levels of F-actin in cones and, furthermore, this F-actin is disorganized [38]. Somewhat surprisingly, dimerization of the myosin-6 heavy chain is not required for myosin-6 function in cones [39], which implies that transport activity is not likely to be important because dimerization is required for normal motor function in vitro . This finding is also consistent with the observation that the rate of cone movement does not differ between wild-type and mutant embryos.…”
Section: Unconventional Functions For Unconventional Myosinsmentioning
confidence: 99%